2015
DOI: 10.5588/ijtld.15.0253
|View full text |Cite
|
Sign up to set email alerts
|

Improved diagnostic sensitivity for tuberculous meningitis with Xpert<SUP>®</SUP> MTB/RIF of centrifuged CSF

Abstract: Introduction TB meningitis (TBM) diagnosis is difficult and novel diagnostic methods are needed. The World Health Organization recommends Xpert MTB/RIF (Xpert) as the initial TBM diagnostic test, based on two studies reporting suboptimal sensitivity (~50–60%). Objective To study the effect of cerebrospinal fluid (CSF) centrifugation on Xpert performance for TBM detection. Design 107 predominantly HIV-infected adults with suspected meningitis were screened prospectively in Kampala, Uganda. CSF was tested by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 25 publications
6
99
0
2
Order By: Relevance
“…This is consistent with prior findings and is likely due to the relatively higher sensitivity of culture versus Xpert, and the ability of Xpert to detect dead TB bacilli 13, 27 . Neither test performed better than the other (P=0.42).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is consistent with prior findings and is likely due to the relatively higher sensitivity of culture versus Xpert, and the ability of Xpert to detect dead TB bacilli 13, 27 . Neither test performed better than the other (P=0.42).…”
Section: Discussionsupporting
confidence: 91%
“…Subjects had comprehensive testing for TBM with CSF AFB smear (Mulago Hospital only), Xpert MTB/Rif on large volume centrifuged CSF 13 and CSF Mycobacteria Growth Inhibitor Tube culture (MGIT, Becton Dickinson, Franklin Lakes, USA). AFB smear was discontinued in Mbarara in 2013 as the sensitivity was deemed too low to justify further use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among participants without cryptococcal meningitis (who require large volume lumbar punctures for control of intracranial pressure), testing of at least 6 mL of CSF (median 10 mL [IQR [8][9][10][11][12]) was associated with a tuberculous meningitis diagnosis (19 [26%] of 73) compared with less than 6 mL (4 mL [3-5mL]; 3 [7%] of 43; p=0·014)].…”
Section: Resultsmentioning
confidence: 99%
“…11,12 A third Ugandan study reported 28% sensitivity with 2 mL of uncentrifuged CSF and 72% sensitivity when centrifuging a median volume of 6 mL (IQR 4-10) with Xpert. 12 Thus, the imperfect sensitivity has meant no test can exclude tuberculous meningitis. 13,14 The Xpert MTB/RIF Ultra (Xpert Ultra) is a new, fully automated, nested real-time PCR assay for the GeneXpert platform.…”
Section: Introductionmentioning
confidence: 99%